Differentiation of olive oils based on rheological and sensory characteristics obtained from six olive cultivars - Dagdelen, A.; Ozkan, G.; Karasu, S.; Sagdic, O. (WAGENINGEN ACADEMIC PUBLISHERS, 2016)
This study was conducted to differentiate between olive oils obtained from different cultivars, namely, Arbequina, Memecik, Uslu, Domat, Hojiblanca and Gemlik, based on their pigment concentration, phenolic and volatile profiles and rheological properties. The phenolic and volatile profiles and rheological and sensorial properties of olive oils obtained from these olive cultivars were compared in this study. Tyrosol and hydroxytyrosol were found to be the most abundant phenolic compounds and determined to be 0.80-14.81 mg/kg and 0.24-13.82 mg/kg, respectively. Of the six cultivars, Gemlik had the highest concentrations of both tyrosol and hyrdoxytyrosol. Additionally, 44 different volatile compounds were identified and their distributions significantly differed across the six cultivars. A steady shear test was conducted to determine flow behaviour properties of olive oil samples, and results revealed that their viscosity values did not significantly differ and ranged from 0.0574 to 0.0610 Pa.s (P<0.05).
Keywords: olive oils; phenolics; rheology; sensorial; volatile compounds; OLEA-EUROPAEA L.; PHENOLIC-COMPOUNDS; QUALITY; PARAMETERS; PROFILES; CORNICABRA; PIGMENTS; COLOR; Food Science & Technology